Transformation of the Castle as Romantic Symbol to Phenomenon of History - Černiauskas, Norbertas (Lietuvos istorijos studijos, 2015)
On the Defence of Vytautas Volungevičius’ Doctoral Thesis „The Castle and It’s Socio-political Transformations in the Grand Duchy of Lithuania during the Period of the 14th–the First Half of 16th c.“